2010
DOI: 10.1038/sj.bjc.6605597
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive factors and risks of biliary tract cancers and stones: a population-based study in Shanghai, China

Abstract: BACKGROUND: Parity has been linked to gallbladder cancer and gallstones, but the effects of other reproductive factors are less clear. METHODS: We examined 361 incident biliary tract cancer cases, 647 biliary stone cases, and 586 healthy women in a population-based study in Shanghai. RESULTS: The effects of parity (odds ratios, OR X3 vs 1 child ¼ 2.0, 95% confidence interval (CI) 0.7 -5.1), younger age at first birth (OR per 1-year decrease ¼ 1.2, 95% CI 0.99 -1.6), and older age at menarche (OR per 1-year in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 48 publications
5
36
3
Order By: Relevance
“…Recent evidence from epidemiological studies has suggested that reproductive factors may be an important risk factor for GBC development [7,8]. A recent populationbased study in Sweden confirmed that high parity and sex hormones may play a role in the etiology of GBC [9].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Recent evidence from epidemiological studies has suggested that reproductive factors may be an important risk factor for GBC development [7,8]. A recent populationbased study in Sweden confirmed that high parity and sex hormones may play a role in the etiology of GBC [9].…”
Section: Introductionmentioning
confidence: 95%
“…After the initial screening, eighteen potentially relevant full publications [8][9][10][11][12][13][18][19][20][21][22][23][24][25][26][27][28][29] were identified from 1412 articles. One publication [24] was considered a conference abstract and was, therefore, excluded from the analysis.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most epidemiological studies assessing the association of endogenous estrogen and BTC have found that factors associated with prolonged exposure to estrogen, i.e. high parity, younger age at birth of the first child, younger age at menarche, increase the risk of BTC [8,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind this sex difference is unknown but it has been hypothesized that exposure to female sex hormones, such as estrogen, might increase this risk [8]. Previous epidemiologic studies addressing this hypothesis have mainly investigated reproductive factors or menstrual history in women, and it seems that high parity and young age at the first birth may increase the risk of BTC [8][9][10][11][12]. However, a recent study by our research group did not support this hypothesis for EHCC, but the role of sex hormones in the risk of GBC could not be ruled out [13].…”
mentioning
confidence: 99%